Portugal : Financial Sector Assessment Program; Technical Note; Stress Testing. (IMF Staff Country Reports; Country Report ;, 2007)
This technical note explains stress testing for Portugal's financial sector. A core part of the banking stress tests was the bottom-up exercise implemented by individual institutions. The bottom-up stress tests focus only on the impact of expected losses on indicators of profitability and capitalization. The results are presented in terms of the actual solvency levels before and after the shock, allowing for an assessment of the capacity of banks to withstand the shocks.